Synergistic antitumor activity of rapamycin and EF24 via increasing ROS for the treatment of gastric cancer - Chen, Weiqian (Redox Biol, 2016)
Mechanistic/mammalian target of rapamycin (mTOR) has emerged as a new potential therapeutic target for gastric cancer. Rapamycin and rapamycin analogs are undergoing clinical trials and have produced clinical responses in a subgroup of cancer patients. However, monotherapy with rapamycin at safe dosage fails to induce cell apoptosis and tumor regression which has hampered its clinical application. This has led to the exploration of more effective combinatorial regimens to enhance the effectiveness of rapamycin. In our present study, we have investigated the combination of rapamycin and a reactive oxygen species (ROS) inducer EF24 in gastric cancer. We show that rapamycin increases intracellular ROS levels and displays selective synergistic antitumor activity with EF24 in gastric cancer cells. This activity was mediated through the activation of c-Jun N terminal kinase and endoplasmic reticulum stress (ER) pathways in cancer cells. We also show that inhibiting ROS accumulation reverses ER stress and prevents apoptosis induced by the combination of rapamycin and EF24. These mechanisms were confirmed using human gastric cancer xenografts in immunodeficient mice. Taken together, our work provides a novel therapeutic strategy for the treatment of gastric cancer. The work reveals that ROS generation could be an important target for the development of new combination therapies for cancer treatment.